Synthesis of carboxylated styrene polymer for internal calibration of Fourier transform ion cyclotron resonance mass-spectrometry of humic substances. Issue 4 (August 2017) - Zherebker, Alexander; Turkova, Alexandra V; Kostyukevich, Yury; Kononikhin, Alexey; Zaitsev, Kirill V; Popov, Igor A; Nikolaev, Eugene; Perminova, Irina V
We report synthesis and application of the novel carboxylated styrene for internal calibration of Fourier transform ion cyclotron resonance mass-spectra of humic substances. The calibrant was synthesized in five steps from acetylsalicylic acid (aspirin) followed by spontaneous polymerization of vinyl salicylic acid. Aromatic nature of the prepared polymer enabled its simultaneous analysis in the presence of the Suwannee River fulvic acid without using dual-spray approach. The major advantage of the calibrant proposed in this study is a lack of suppression of humic substances signals and maintenance of peak intensity distribution. The appropriate calibration resulted in an increased number of unambiguous identification in Suwannee River fulvic acid. Thanks to the higher mass accuracy, it was also possible to refine attribution of the CHOS species to hydrolysable tannins as opposed to the erroneous previous assignment to the condensed tannins.